Factors responsible for early postoperative mental alterations after bilateral implantation of subthalamic electrodes - Hrabovsky, D; Balaz, M; Rab, M; Feitova, V; Hummelova, Z; Novak, Z; Chrastina, J (British journal of neurosurgery, 2017)
INTRODUCTION: Early postoperative mental changes are the most frequent problem after bilateral subthalamic electrode implantation. The study aims to find an association between them and factors related to patient, disease and surgery, including the size of the third ventricle as brain atrophy marker. MATERIAL AND METHODS: The study included 80 patients with bilateral subthalamic electrodes implanted for motor complications of Parkinson's disease (PD). Patients' age, disease and motor complications duration, medication, neuropsychological tests, surgical reports, third ventricle length (intercommissural distance) and width (intermammillary distance) were analysed. RESULTS: Early mental alterations requiring treatment were observed in 25.0% of patients with higher age being significant predictor. The duration of PD motor complications, L DOPA equivalent dose, DSR Mattis, third ventricle length and width were not statistically significant predictors. The incidence of postoperative mental alteration with intermammillary distance > 8 mm was 60%. The percentage of left sided electrodes implanted in anterior trajectory is significantly higher in patients with early mental changes. CONCLUSIONS: Higher age is a risk factor for early postoperative mental changes, but not disease, late motor complications duration and parameters describing third ventricular size except the excessive intermammillary distance. Left sided electrode implanted in anterior position is a risk factor.
Keywords: implantované elektrody; Magnetic Resonance Imaging; magnetická rezonanční tomografie; Humans; neuropsychologické testy; třetí mozková komora; lidé středního věku; Deep Brain Stimulation; early postoperative mental changes; Female; rizikové faktory; Aged; Deep brain stimulation; věkové faktory; senioři; lidé; nucleus subthalamicus; levodopa; Antiparkinson Agents; duševní poruchy; Parkinson’s disease; Postoperative Complications; pooperační komplikace; Electrodes, Implanted; ženské pohlaví; Neuropsychological Tests; Third Ventricle; Male; Middle Aged; Levodopa; hluboká mozková stimulace; antiparkinsonika; Aged, 80 and over; Subthalamic Nucleus; Mental Disorders; senioři nad 80 let; Age Factors; mužské pohlaví; brain atrophy; Parkinson Disease; subthalamic nucleus; Risk Factors; Parkinsonova nemoc